If ϕ = n + n + n + . . . , where ϕ represents 2 1 + 5 , and 3 n − n i n + n i is a complex number which can be solved to equal c a + b i , where i 2 equals − 1 and a , b and c are positive integers, find the value of ( a + b + c ) a + b c ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
What a nice final expression.
It is "quite known" that φ = 1 + 1 + ⋯ . Thus n = 1 .
Simplifying 3 − i 1 + i , we have ( 3 − i ) ( 3 + i ) ( 1 + i ) ( 3 + i ) = c a + b i ⇒ 1 0 2 + 4 i = c a + b i and thus a = 1 , b = 2 , c = 5 .
For it the final expression becomes ( 1 + 2 + 5 ) 1 + 2 5 ⇒ 2 3 ⋅ 3 5 ⇒ 3 2 .
Note that n is non-zero, so 3 n − n i n + n i automatically simplifies to 3 − i 1 + i .
Given that ϕ = 2 1 + 5 and 3 n − n i n + n i is a complex no. which can be solved down to c a + b i . So, at first we have ---
ϕ = n + n + n + . . . . .....(i)
ϕ 2 = n + n + n + n + . . . . [Squaring both sides]
ϕ 2 = n + ϕ [From (i)]
( 2 1 + 5 ) 2 = n + ( 2 1 + 5 )
4 1 + 2 5 + 5 = 2 2 n + 1 + 5
2 2 5 + 6 = 2 n + 1 + 5 ⟹ 4 n + 2 + 2 5 = 6 + 2 5 ⟹ 4 n = 4 ⟹ n = 4
Then, the complex no. in the question is 3 n − n i n + n i = 3 − i 1 + i . Then, we solve this as follows --
3 − i 1 + i
= ( 3 − i ) ( 3 + i ) ( 1 + i ) ( 3 + i )
= 3 2 − i 2 3 + i + 3 i + i 2 [Using the identity a 2 − b 2 = ( a + b ) ( a − b ) ]
= 9 + 1 3 + 4 i − 1 [since i 2 = ( − 1 ) ]
= 1 0 2 + 4 i = 1 0 2 ( 1 + 2 i ) = 5 1 + 2 i
So, we have the complex no. in c a + b i form with a = 1 , b = 2 , c = 5 . Then, we have ---
( a + b + c ) a + b c = ( 1 + 2 + 5 ) 1 + 2 5 = ( 8 ) 3 5 = ( 2 3 ) 3 5 = ( 2 ) 3 × 3 5 = 2 5 = 3 2
ϕ = s q r t ( n + s q r t ( n + . . . ) )
Thus, ϕ = s q r t ( n + ϕ ) .
Squaring both sides: ϕ 2 = n + ϕ .
Since ϕ 2 = ϕ + 1 , we can conclude that n = 1 .
Our complex number is then ( 1 + i ) / ( 3 − i ) . Multiplying this by ( 3 + i ) / ( 3 + i ) yields: ( 2 + 4 i ) / ( 1 0 ) = ( 1 + 2 i ) / 5 . You should have been more careful when you stated that the complex number can be represented as ( a + b i ) / c , since there are infinite representations that are of the form ( n a + n b i ) / n c , n a nonzero real number, which equal the complex number you gave us - and those will yield different results. I'll assume that you wanted us to consider a = 1, b = 2 and c = 5. Then the answer would be ( 1 + 2 + 5 ) ( 5 / ( 1 + 2 ) ) , which equals 8 5 / 3 , or 2 5 , which is 3 2
Problem Loading...
Note Loading...
Set Loading...
If we square the given expression we get:
ϕ 2 = n + n + n + . . . . . .Take n to the left side and we have:
ϕ 2 − n = n + n + . . . . . .But n + n + . . . . = ϕ , therefore our equation transforms into :
ϕ 2 − n = ϕ where ϕ 2 = ϕ + n .We know that ϕ satisfies the equation ϕ 2 = ϕ + 1 and equating this to our equation we easily get n = 1 .From this we know our complex number is :
3 − i 1 + i .Multiplying both the numerator and the denominator by 3 + i our complex number bcomes :
( 3 − i ) ( 3 + i ) ( 1 + i ) ( 3 + i ) = 1 0 4 i + 2 = 5 2 i + 1 .Thus a = 1 , b = 2 and c = 5 .And we have ( a + b + c ) a + b c = 8 3 5 = 3 2 .